2014
DOI: 10.1371/journal.pgen.1004656
|View full text |Cite
|
Sign up to set email alerts
|

SPDEF Inhibits Prostate Carcinogenesis by Disrupting a Positive Feedback Loop in Regulation of the Foxm1 Oncogene

Abstract: SAM-pointed domain-containing ETS transcription factor (SPDEF) is expressed in normal prostate epithelium. While its expression changes during prostate carcinogenesis (PCa), the role of SPDEF in prostate cancer remains controversial due to the lack of genetic mouse models. In present study, we generated transgenic mice with the loss- or gain-of-function of SPDEF in prostate epithelium to demonstrate that SPDEF functions as tumor suppressor in prostate cancer. Loss of SPDEF increased cancer progression and tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 46 publications
3
95
0
Order By: Relevance
“…The absence of H3K4me3 in the normal liver may ensure that the liver cells would not enter into cell cycle under normal conditions. Whereas FOXM1 activates its own expression, the Ets-related transcription factor SPDEF inhibits the Foxm1 promoter activity (32). Interestingly, the mRNA expression of SPDEF was induced in the RL (Fig.…”
Section: The Integration Of the Cistrome And The Transcriptome Pointsmentioning
confidence: 92%
“…The absence of H3K4me3 in the normal liver may ensure that the liver cells would not enter into cell cycle under normal conditions. Whereas FOXM1 activates its own expression, the Ets-related transcription factor SPDEF inhibits the Foxm1 promoter activity (32). Interestingly, the mRNA expression of SPDEF was induced in the RL (Fig.…”
Section: The Integration Of the Cistrome And The Transcriptome Pointsmentioning
confidence: 92%
“…cDNA was generated using the Applied Biosystems High Capacity cDNA reverse transcription kit (Applied Biosystems, Foster City, CA). Evaluation of expression levels of specific genes was performed by qRT-PCR using inventoried TaqMan probes (Table 2) and the StepOnePlus real-time PCR system (Applied Biosystems, Foster City, CA) as described previously (37)(38)(39)(40)(41)(42).…”
Section: Primer Name Sequencementioning
confidence: 99%
“…They showed that the tumor suppressor SPDEF competed with FOXM1 for the FOXM1 binding site responsible for the autoregulation of FOXM1. Furthermore, SPDEF inhibited FOXM1 expression and consequently cancer development in a mouse model of prostate cancer (33). These data suggest that the autoregulation of FOXM1 might be required for cancer development and could be a promising target for anticancer treatment.…”
Section: Discussionmentioning
confidence: 74%
“…1 and 4E). Recently, Cheng et al (33) confirmed the importance of FOXM1 autoregulation for cancer development (34). They showed that the tumor suppressor SPDEF competed with FOXM1 for the FOXM1 binding site responsible for the autoregulation of FOXM1.…”
Section: Discussionmentioning
confidence: 96%